Early social-cognitive development as a dynamic developmental system—a lifeworld approach - Kärtner, Joscha; Köster, Moritz (Frontiers in Psychology, 2024)
Based on developmental systems and dynamic systems theories, we propose the lifeworld approacha conceptual framework for research and a hypothesis concerning early social-cognitive development. As a framework, the lifeworld approach recognizes the social embeddedness of development and shifts the focus away from individual developmental outcomes toward the reciprocal interplay of processes within and between individuals that co-constitutes early socialcognitive development. As a hypothesis, the lifeworld approach proposes that the changing developmental system -spanning the different individuals as their subsystems -strives towards attractor states through regulation at the behavioral level, which results in both the emergence and further differentiation of developmental attainments. The lifeworld approach -as a framework and a hypothesis, including key methodological approaches to test it -is exemplified by research on infants' self-awareness, prosocial behavior and social learning. Equipped with, first, a conceptual framework grounded in a modern view on development and, second, a growing suite of methodological approaches, developmental science can advance by analyzing the mutually influential relations between intra-individual and interactional processes in order to identify key mechanisms underlying early social-cognitive development.It is a mantra in the developmental sciences that nature and nurture interact in complex ways in human development. For instance, developmental systems approaches (e.g., Gottlieb, 2007;Overton, 2013;Oyama, 2000) conceive ontogeny as the dynamic interplay of internal and external factors at different levels (e.g., genes, brain, behavior, ecology, culture). Relatedly, transactional theories emphasize that throughout ontogeny there exists a dialectic interplay of nature and nurture (e.g., Sameroff, 2009).Yet, many contemporary theories in developmental psychology focus on the development of the individual without taking into full account that social-cognitive development is deeply embedded in hat gelöscht: a hat gelöscht: is 36 hat gelöscht: data hat gelöscht: in closing this conceptual gap